Development of Information Management System for Food Donation Distribution - Muniandy, Thivyanath; Nureize Arbaiy (Applied Information Technology And Computer Science, 2022)
This paper describes the development of a food donation distribution system that aims to improve the information management process for donation and distribution to those in need by utilizing information technology and databases. Non-governmental organizations (NGOs) currently maintain track of donations using Excel spreadsheets. It is highly susceptible to human error. Because spreadsheets are open to manipulation and are not secured, there is a risk of data corruption. As a result, a food donation distribution information management system is proposed to address the issues while also providing a means to improve the efficiency of the current management process. This system was created using Visual Studio Code, XAMPP, and the Microsoft Windows 10 operating system. The PHP programming language was used to create the system. The prototype technique is utilized to oversee project development implementation. The outcomes of the study will have a positive impact on commonly used procedures, particularly in the process of NGOs managing food donation information.